Coronary heart disease in women: a challenge for the 21st century (Clinics, 2010)
Heart disease is the first killer of women in the modern era, regardless of age, race and of ethnicity, although its prevalence rises after menopause. Modern women have professional and housewife responsibilities, consume excess of fat and carbohydrates, smoke, do not exercise regularly and do not have enough time to rest. This situation leads to overweight, dyslipidemia, arterial hypertension, impaired glucose tolerance and diabetes. Women do not often participate in preventive studies and still undergo less intensive and invasive evaluation and treatment for chest pain when compared to men. However, the rate of coronary death is twice higher in women than in men after myocardial infarction and revascularization procedures. The objective of this review is to analyze the main gender differences regarding symptoms, diagnosis, management and prognosis of coronary heart disease and to discuss the influence of hormonal replacement therapy in the prevention of cardiovascular disease in postmenopausal women.